Choosing the best route: Comparative optimization of wheat transformation methods for improving yield by targeting TaARE1-D with CRISPR/Cas9 - Mumin Ibrahim Tek; Kubra Budak Tek; Pelin Sarikaya; Abdul Razak Ahmed; Hakan Fidan (PLoS ONE, 2026)
Wheat ( Triticum aestivum L.) is one of the most important crops worldwide, supplying a major share of calories and protein for the global population. Incorporating gene editing into breeding programs is critical to improve yield and stress tolerance, yet wheat remains difficult to transform and regenerate efficiently. These bottlenecks limit the full application of CRISPR/Cas9 for improvement yield in wheat. To address this, transformation parameters were optimized for three methods: immature embryo transformation, callus transformation, and injection-based in planta transformation. Systematic optimization of Agrobacterium strain, bacterial density, acetosyringone concentration, and incubation conditions resulted in substantially improved transformation success. Efficiencies of 66.84% for immature embryos, 55.44% for callus, and 33.33% for in planta transformation were achieved, representing more than tenfold increase compared with previously reported rate of ~3%. A key innovation was the shortening of the callus induction stage for immature embryos, reducing the time required for plant regeneration by approximately one month while maintaining high transformation efficiency. The protocols were validated through CRISPR/Cas9-mediated knockout of TaARE1-D , a negative regulator of nitrogen uptake and yield. Generated mutants exhibited increased grain number, spike length, grain length, and thousand-grain weight, as well as the characteristic stay-green phenotype associated with loss of TaARE1-D function. The optimized protocols provide robust platforms to accelerate gene-editing in wheat to increase yield and stress-tolerance.